Medical use and costs for native fathers and children from transnational marriage families in Taiwan from 2004 to 2017 - Chen, Yi-Lung (Frontiers in Public Health, 2022)
Objectives This is the first study to examine health care utilization in terms of medical use and costs in native fathers and children from transnational families. Methods Taiwan National Health Insurance Research Database was used to compare the annual medical use and inflation-adjusted medical cost for ambulatory care from 2004 to 2017 between native fathers and children from transnational and native families. Results Native fathers from transnational families had lower annual medical use (−0.23 visits) but higher total medical costs (New Taiwan dollars, NT, 966), especially in dialysis and psychiatry, compared with those from native families. Unlike fathers from transnational families, their children were observed to consistently have lower medical use (−1.35 visits) and costs (NT −636), compared with those from native families. Conclusions There was different medical use and costs in transnational marriage families, possibly as a result of features in transnational marriage families. These findings provide insight for future health care policies to address the different health care utilization by exploring the unmet needs and barriers relating to children and fathers from transnational families.